2020
DOI: 10.1039/d0ra04642f
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-embedded S-doped g-C3N4 heterojunction: mediator-free Z-scheme mechanism for enhanced charge separation and photocatalytic degradation

Abstract: We have developed the LED light active ZnO-embedded S-doped g-C3N4 (SCN) mediator free Z-scheme heterojunction photocatalyst for effective organic pollutant degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Figure 2 h shows the XPS spectrum of Zn 2p, which reveals two peaks at 1020.3 and 1044.8 eV that correspond to the Zn 2p 5/2 and Zn 2p 3/2 , respectively. The Zn 2p spectrum indicates the presence of Zn ions with +2 oxidation states [ 32 ]. The O 1s XPS spectrum is deconvoluted into three peaks at 530, 531.2 and 532.3 eV, which are due to the O 2+ , metal oxides and metal carbonate, respectively [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 h shows the XPS spectrum of Zn 2p, which reveals two peaks at 1020.3 and 1044.8 eV that correspond to the Zn 2p 5/2 and Zn 2p 3/2 , respectively. The Zn 2p spectrum indicates the presence of Zn ions with +2 oxidation states [ 32 ]. The O 1s XPS spectrum is deconvoluted into three peaks at 530, 531.2 and 532.3 eV, which are due to the O 2+ , metal oxides and metal carbonate, respectively [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the diffraction results, it was confirmed that all the samples have an analogous diffraction pattern and it is compatible with the standard JCPDS card (36-1451) and former literature result. 3 The diffraction planes (110), (002), (101), (102), (110), (103), and (112) related to ZnO nanoparticles have the 2 θ values of 31.81, 34.47, 36.32, 47.61, 56.66, 62.91 and 68.04° respectively. Gd doped ZnO shows the relatively low intense XRD peaks, which revealed the doping of Gd ions reduces the crystallinity of ZnO.…”
Section: Resultsmentioning
confidence: 99%
“… 2 Among various semiconducting metal oxide photocatalysts, ZnO is a widely studied photocatalyst due to its non-toxic nature, and excellent electrical, optical, and oxidation-resistant properties. 3 ZnO (n-type semiconductor) has a wide band gap of 3.4 eV with a large excitation binding energy (60 meV) value at ambient temperature. Moreover, ZnO has a higher quantum efficiency compared to TiO 2 in certain cases.…”
Section: Introductionmentioning
confidence: 99%
“…As a promising green technology, the photocatalytic technique has advantages of simple operation, high efficiency, economy, and good recyclability, and is considered as one of the ideal ways to tackle pollution. 6 Some excellent photocatalysts have been developed, such as ZnO, 7 Bi 2 O 3 , 8 CdS, 9 etc. What is more, graphitic carbon nitride (g-C 3 N 4 ), an organic semiconductor photocatalyst, has the advantages of easy preparation, low cost, and visible light response.…”
Section: Introductionmentioning
confidence: 99%